ҚАРАҚАЛПАҚ ПРОЗАСЫНДА ГҮРРИҢ ЖАНРЫНДА ДЕТЕКТИВ ФОРМАЛАРДЫҢ БЕРИЛИЎИ - Алламуратова, З. (FAN va JAMIYAT, 2023)
The article examines the use of detective forms in the narrative genre in Karakalpak prose. During the period of independence, examples were taken from the works of great writers of Karakalpak literature.